2022
DOI: 10.1136/bmjoq-2021-001775
|View full text |Cite
|
Sign up to set email alerts
|

Quality improvement initiative to improve the duration of Kangaroo Mother Care in tertiary care neonatal unit of South India

Abstract: BackgroundIndia has the highest number of preterm births and maximum number of deaths due to prematurity. Chengalpattu Government Medical College had 11 593 deliveries annually in 2020, of which 2252 of neonates were low birth weight. 2016 Cochrane review concluded that Kangaroo Mother Care (KMC) reduces the morbidity and mortality in low birthweight infants. The average duration of KMC in our unit was around 4.6 hours/baby/day.ObjectiveTo improve the duration of KMC in stable low birthweight babies from short… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…A study across seven sites in Ethiopia and India reported that 60% of eligible infants received KMC with ≥ 8 h of skin-to-skin contact and exclusive breastfeeding in the 24 h preceding discharge, and that this coverage was achieved with government engagement and financial resources to establish and maintain KMC units with supportive policies for mothers, including beds, food, bathing, and toilets [ 40 ]. In contrast, the WHO trial and a related quality improvement study reported a median daily duration of skin-to-skin contact of 17 h among babies who received iKMC, following the establishment of mother-neonatal intensive care units with adult beds for KMC in six tertiary-level hospitals in Ghana, India, Malawi, Nigeria, and Tanzania [ 17 , 41 ], illustrating the importance of providing infrastructure and advanced newborn care and equipment, including CPAP.…”
Section: Discussionmentioning
confidence: 99%
“…A study across seven sites in Ethiopia and India reported that 60% of eligible infants received KMC with ≥ 8 h of skin-to-skin contact and exclusive breastfeeding in the 24 h preceding discharge, and that this coverage was achieved with government engagement and financial resources to establish and maintain KMC units with supportive policies for mothers, including beds, food, bathing, and toilets [ 40 ]. In contrast, the WHO trial and a related quality improvement study reported a median daily duration of skin-to-skin contact of 17 h among babies who received iKMC, following the establishment of mother-neonatal intensive care units with adult beds for KMC in six tertiary-level hospitals in Ghana, India, Malawi, Nigeria, and Tanzania [ 17 , 41 ], illustrating the importance of providing infrastructure and advanced newborn care and equipment, including CPAP.…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Ramachandrappa et al, using three PDSA cycles, the duration of KMC at the institute was increased from 2.7 hours/baby/day to 7.8 hours/baby/day [ 15 ]. In the study by Jegannathan et al, the duration of KMC was improved from 4.6 hours/baby/day to 16.6 hours/baby/day by implementing seven PDSA cycles [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mother/alternative KMC provider-Baby dyads were classified as A, B, C, and D based on the last 48 hours of KMC performance. The KMC duration was classified into four categories: short, extended, long, and continuous where KMC provided 4 hours/day, 5-8 hours/day, 9-12 hours/day, and more than 12 hours/day respectively [ 13 ]. Before embarking on the study, we carried out a fishbone analysis, and a series of plan-do-study-act (PDSA) cycles were planned based on the needs analysis (Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…A qualitative study by Jegannathan et al showed improvement from 4.6 hours/day to an impressive 16.6 hours/ day with these interventions. 26 Longer duration of KMC sessions achieved by practicing milk expression in the KMC position and doing simple procedures during skin-to-skin contact are associated with reduced mortality and better growth. 27,28 The current survey revealed 40.4% NICUs have supported mothers for expressing milk in KMC position.…”
Section: (Table 2 Continued) (Table 2 Continued)mentioning
confidence: 99%